Accounting for metal bioavailability in assessing water quality: A step change?. (25th January 2016) - Merrington, Graham; Peters, Adam; Schlekat, Christian E.
Abstract: Bioavailability of metals to aquatic organisms can be considered to be a combination of the physicochemical factors governing metal behavior and the specific pathophysiological characteristics of the organism's biological receptor. Effectively this means that a measure of bioavailability will reflect the exposures that organisms in the water column actually "experience". This is important because it has long been established that measures of total metal in waters have limited relevance to potential environmental risk. The concept of accounting for bioavailability in regard to deriving and implementing environmental water quality standards is not new, but the regulatory reality has lagged behind the development of scientific evidence supporting the concept. Practical and technical reasons help to explain this situation. For example, concerns remain from regulators and the regulated that the efforts required to change existing systems of metal environmental protection that have been in place for over 35 yr are so great as not to be commensurate with likely benefits. However, more regulatory jurisdictions are now considering accounting for metal bioavailability in assessments of water quality as a means to support evidence‐based decision‐making. In the past decade, both the US Environmental Protection Agency and the European Commission have established bioavailability‐based standards for metals, including Cu and Ni. These actions have shifted the debate toward identifying harmonized approaches for determining when knowledge is adequate to establish bioavailability‐based approaches and how to implement them. Environ Toxicol Chem 2016;35:257–265. © 2016 SETAC